2010
DOI: 10.1371/journal.pone.0011391
|View full text |Cite
|
Sign up to set email alerts
|

UCP1 Induction during Recruitment of Brown Adipocytes in White Adipose Tissue Is Dependent on Cyclooxygenase Activity

Abstract: BackgroundThe uncoupling protein 1 (UCP1) is a hallmark of brown adipocytes and pivotal for cold- and diet-induced thermogenesis.Methodology/Principal FindingsHere we report that cyclooxygenase (COX) activity and prostaglandin E2 (PGE2) are crucially involved in induction of UCP1 expression in inguinal white adipocytes, but not in classic interscapular brown adipocytes. Cold-induced expression of UCP1 in inguinal white adipocytes was repressed in COX2 knockout (KO) mice and by administration of the COX inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
165
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 182 publications
(176 citation statements)
references
References 59 publications
9
165
1
1
Order By: Relevance
“…S1). Rosi and PGE2 have adipose tissue browning effects, which can induce adipose tissue transformation and angiogenesis (17,21). The NPs containing Rosi have an average size of 100 nm ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S1). Rosi and PGE2 have adipose tissue browning effects, which can induce adipose tissue transformation and angiogenesis (17,21). The NPs containing Rosi have an average size of 100 nm ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Rosi has been reported to stimulate PPAR activity, which leads not only to adipose tissue transformation by increasing the expression levels of uncoupling proteins but also activates angiogenesis in adipose tissue by elevating expression levels of VEGF and angiopoietin-like 4 (14)(15)(16). PGE2 has been shown to activate the prostaglandin receptor, which promotes adipose tissue transformation by increasing the expression of Uncoupling protein 1 (UCP1) (17). We show that peptide-conjugated NPs effectively deliver Rosi and PGE2 into adipose tissues while minimizing adverse effects on other tissues.…”
Section: Significancementioning
confidence: 99%
“…Recent studies [44,45] demonstrated the involvement of COX-2 in the induction of these fatburning cells and the importance of the COX-2-mediated mechanisms for the resistance to dietary obesity in mice. Our results convincingly demonstrate a marked induction of mitochondrial oxidative capacity in permeabilised adipocytes isolated from epididymal fat in response to mild calorie restriction combined with LC n-3 PUFA intake, using succinate as the optimum fuel [46].…”
Section: Discussionmentioning
confidence: 99%
“…Parts of the eWAT were subjected to standard hematoxylin and eosin staining as described previously (40).…”
Section: Methodsmentioning
confidence: 99%